2013
DOI: 10.1002/lary.24275
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measurements in obstructive sleep apnea: Beyond the apnea‐hypopnea index

Abstract: The literature shows a range of tools based on symptoms and physiology of OSA that can assess effects of treatment. Assessment of surgical treatment for OSA should neither be limited to AHI as an outcome, nor should this be the only outcome stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
(118 reference statements)
3
38
0
1
Order By: Relevance
“…Additionally, PSG parameters including AHI, AI, RDI, and supine AI also significantly improved postoperatively compared to those in preoperative PSG regardless of using AASM 2007Rec and AASM 2012Rec criteria. Our results support other previous studies showing that the surgical treatment is effective in improving the subjective symptoms as well as objective severity of OSA . Furthermore, our results demonstrated significant differences in the AHI, HI, RERA, RDI, and supine AHI between AASM 2007Rec and AASM 2012Rec criteria.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, PSG parameters including AHI, AI, RDI, and supine AI also significantly improved postoperatively compared to those in preoperative PSG regardless of using AASM 2007Rec and AASM 2012Rec criteria. Our results support other previous studies showing that the surgical treatment is effective in improving the subjective symptoms as well as objective severity of OSA . Furthermore, our results demonstrated significant differences in the AHI, HI, RERA, RDI, and supine AHI between AASM 2007Rec and AASM 2012Rec criteria.…”
Section: Discussionsupporting
confidence: 91%
“…Optimal treatment for OSA is as critical as prompt diagnosis for improved patients’ health and quality of life. The optimal treatment method is generally determined according to the patient's anatomical structures, PSG parameters, and personal preferences . Additionally, the success rate of each treatment option is one of the factors that can be considered to choose the proper treatment option for OSA patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies have shown that AHI is poorly associated with many of the classical symptoms and the physiology of OSA as measured by, for example, quality of life, sleepiness and performance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence has shown significant discordance between the levels of AHI used to denote outcomes of therapy and real world clinical outcomes such as QOL, patient perception of disease, cardiovascular measures, disease burden and/or survival [1][2][3][4][5]. There is a mountain of evidence showing how the AHI can vary from night to night, vary from laboratory to laboratory, from various nasal thermistor to pressure transducers, and AHI can vary based on the different definitions of hypopnea used in different laboratories and software [6][7][8][9][10][11][12][13][14].…”
Section: Dear Editormentioning
confidence: 99%